Self-motion behaviors of kinematically redundant manipulator for continuous path planning - Setyamartana Parman; Mahmud Iwan Solihin (Faculty of Advanced Technology and Multidiscipline Universitas Airlangga, 2022)
This paper presents self-motion behaviors of 3-DOF planar robotic arm when it tracks a predefined end-effector path. In this case, the self-motion contributes to geometry of a motion envelope. The Bezier curve degree fifth is utilized as the tracked path. Different geometry of the motion envelope can be used to avoid collision while it also follows the tracked path accurately. A theta global as closed form solution of 3-DOF planar robot is modeled as a polynomial degree sixth. A Genetic Algorithm (GA) as one of meta-heuristic optimizations is used to find optimal solution of the path planning approach. An effect of initial and final joint angles in the robotic arm motion is also investigated. The theta global trajectories are also possible to contain an imaginary number. The imaginary number of the theta global trajectories can be used as a sign that position errors are present and the trajectories need to be repaired using the self-motion analysis.